An Islam and the Capacity of the Democratic Regime in Indonesia in the Reformation Era - Luthfi Hasanal Bolqiah (Program Studi Ilmu Politik Fakultas Ilmu Sosial dan Ilmu Politik Universitas PGRI Ronggolawe Tuban, 2023)
This article aims to explain the role of Islamic institutions in the capacity of a democratic government, namely Indonesia, in meeting the basic needs of its citizens. Islam is often considered the main contributor to the recession or setback of democracy in Indonesia. However, this view generally only sees Islam in the context of state autonomy or as a tool to legitimize power. The method used is a literature study with the theory of autonomy and state capacity according to Patrick O'Neil. The results of the study show that Islamic political, social, and economic institutions play a major role in the low state autonomy because Islamic involvement legitimizes the Indonesian democratic regime. However, these three Islamic institutions have also contributed to the low capacity of the Indonesian democratic regime to carry out basic tasks and provide security and peace, freedom, and equality. This article is limited to the macro data used in the analysis and the limitations of the institutional approach.